Modeling and nonlinear dynamics of thermomechanically coupled composite plates. (1st December 2020) - Rega, Giuseppe; Saetta, Eduardo; Settimi, Valeria
Highlights: Thermomechanically coupled models constructed through a unified 2D formulation. Minimal ROMs obtained and a reach yet cheap one selected for nonlinear dynamics. Local and global dynamics analyzed for various boundary/body thermal excitations. Complex interactions phenomena in slow-fast dynamics unveiled via global analysis. Thermomechanical coupling effects addressed along with possible further reductions. Graphical abstract: Image, graphical abstract Abstract: An overview of extended research recently pursued on unified continuous/reduced-order modeling and nonlinear dynamics of thermomechanical composite plates of interest in aerospace, mechanical and civil engineering is presented. Reduced models exhibit the fundamental features of geometrical nonlinearity and thermomechanical coupling of the underlying continua. The role of multiphysics coupling and the main features of nonlinear response obtained with variably refined minimal models is highlighted. Besides transverse mechanical excitation and mechanically or thermally-induced buckling, a variety of active thermal excitations, of body or boundary nature, are considered. Features of thermal response obtained with variably refined thermal assumptions are compared, in view of detecting cheap, yet reliable, models to be used for systematic numerical investigations. The effects of two-way thermomechanical coupling on local and global nonlinear dynamics are addressed through bifurcation diagrams, phase portraits and planar cross sections of 4D basins of attraction, highlighting the important role played by the slow transient thermal dynamics solely detectable with coupled models in the steady outcome of the swifter mechanical response. Conditions allowing to utilize partially coupled models or even the uncoupled mechanical one with prescribed steady temperature are discussed.